Multiple relaxases contribute to the horizontal transfer of the virulence plasmids from the tumorigenic bacterium Pseudomonas syringae pv. savastanoi NCPPB 3335 - Añorga, Maite; Urriza, Miriam; Ramos, Cayo; Murillo, Jesús (Frontiers in Microbiology, 2022)
Pseudomonas syringae pv. savastanoi NCPPB 3335 is the causal agent of olive knot disease and contains three virulence plasmids: pPsv48A (pA), 80 kb; pPsv48B (pB), 45 kb, and pPsv48C (pC), 42 kb. Here we show that pB contains a complete MPFT (previously type IVA secretion system) and a functional origin of conjugational transfer adjacent to a relaxase of the MOBP family; pC also contains a functional oriT -MOBP array, whereas pA contains an incomplete MPFI (previously type IVB secretion system), but not a recognizable oriT. Plasmid transfer occurred on solid and in liquid media, and on leaf surfaces of a non-host plant (Phaseolus vulgaris) with high (pB) or moderate frequency (pC); pA was transferred only occasionally after cointegration with pB. We found three plasmid-borne and three chromosomal relaxase genes, although the chromosomal relaxases did not contribute to plasmid dissemination. The MOBP relaxase genes of pB and pC were functionally interchangeable, although with differing efficiencies. We also identified a functional MOBQ mobilization region in pC, which could only mobilize this plasmid. Plasmid pB could be efficiently transferred to strains of six phylogroups of P. syringae sensu lato, whereas pC could only be mobilized to two strains of phylogroup 3 (genomospecies 2). In two of the recipient strains, pB was stably maintained after 21 subcultures in liquid medium. The carriage of several relaxases by the native plasmids of P. syringae impacts their transfer frequency and, by providing functional diversity and redundancy, adds robustness to the conjugation system.